EMPLOYEE PERFORMANCE ANALYSIS BASED ON LEADERSHIP STYLE MEDIATED BY MOTIVATION - Fatkhuri Fatkhuri; Dyah Handayani Dewi; Kevin Indajang; Sri Sudiarti; Novita Sari (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study examines the effect of leadership style on employee performance with work motivation as a mediating variable. In modern organizational environments, leadership has been recognized as a critical determinant of employee performance. Effective leadership fosters a supportive work environment, enhances intrinsic and extrinsic motivation, and ultimately contributes to improved employee performance. Although numerous studies have explored the direct relationship between leadership and performance, few have rigorously assessed the mediating role of motivation using a large, representative sample. This study employed a quantitative approach using the Statistical Package for the Social Sciences (SPSS) and surveyed 100 employees from various departments of PT KLM Tangerang to test the hypothesized relationship. Data were collected through a structured questionnaire and analyzed using regression and mediation analyses. The results indicate that leadership style significantly influences motivation, which in turn positively influences employee performance. Furthermore, motivation partially mediates the relationship between leadership style and performance, suggesting that leadership practices foster higher motivation, which improves performance outcomes. These findings corroborate recent literature demonstrating consistent positive effects of leadership and motivation on performance. This study contributes to organizational behavior theory by providing empirical evidence on the mediating mechanisms of motivation and offers practical implications for human resource management. Organizations should prioritize leadership development programs and motivational strategies to strengthen employee performance and organizational effectiveness.